2005
DOI: 10.1021/ac0502697
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Photoionization for Enhanced Compatibility in On-Line Micellar Electrokinetic Chromatography−Mass Spectrometry

Abstract: Atmospheric pressure photoionization (APPI) is presented as a novel means for the combination of micellar electrokinetic chromatography (MEKC) and mass spectrometry (MS). The on-line coupling is achieved using an adapted sheath flow interface installed on an orthogonal APPI source. Acetone or toluene is added as dopant to the sheath liquid to enhance analyte photoionization. It is demonstrated that with APPI signal suppression and interferences by the surfactant sodium dodecyl sulfate (SDS) and nonvolatile buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…Best responses in APPI were achieved with a SheaF around 50 mL/min. This high SheaF ensured stable spray and best ionization conditions and was in agreement with previous studies where a high SheaF was also selected [43,44]. It must be noted that the optimal value in ESI is quite lower (about 3-5 mL/min).…”
Section: Sensitivity Modelingsupporting
confidence: 89%
See 2 more Smart Citations
“…Best responses in APPI were achieved with a SheaF around 50 mL/min. This high SheaF ensured stable spray and best ionization conditions and was in agreement with previous studies where a high SheaF was also selected [43,44]. It must be noted that the optimal value in ESI is quite lower (about 3-5 mL/min).…”
Section: Sensitivity Modelingsupporting
confidence: 89%
“…The APPI configuration, now commercially available from Agilent [47], was recently investigated by Mol et al [44] and the authors confirmed that a wider choice of CE electrolytes (buffer and additives) could be used for both polar and nonpolar compounds [44]. The study also demonstrated the possiblity to work with micellar EKC (MEKC) and MS [43]. It was concluded that SDS had no negative effect on photoionization efficiency and APPI might provide a good solution for MEKC-MS.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Owing to its capability to form both even-and odd-electron ions, the latter technique was found suitable for ionization of both polar and apolar compounds. Furthermore, APPI appeared to be unaffected by the BGE composition, and even enabled the coupling of micellar electrokinetic chromatography (MEKC) and microemulsion electrokinetic chromatography (MEEKC) with MS [10,11].…”
mentioning
confidence: 99%
“…Therefore, AS11-HC column was selected as the separation column in this experiment. It is reported that the sensitivity can be increased by introducing an organic modifier to enhance the ionization process during ESI [23][24][25][26]. Therefore, the flow rate of methanol with a post-column addition was optimized.…”
Section: Optimization Of the Chromatographic Separationmentioning
confidence: 99%